Children’s social networks in developmental psychology: A network approach to capture and describe early social environments - Burke, Nicole; Brezack, Natalie; Woodward, Amanda (Frontiers in Psychology, 2022)
Psychologists are interested in understanding how early social environments impact children’s behavior and cognition. Early social environments are comprised of social relationships; however, there have been relatively few tools available to quantify the depth and breadth of children’s social relationships. We harnessed the power of social networks to demonstrate that networks can be used to describe children’s early social environments. Descriptive data from American children aged 6 months to 5 years (n = 300; 47% female, 56% White) demonstrates that network properties can be used to provide a quantitative analysis of children’s early social environments and highlights how these environments vary across development. Social network methodology will provide researchers with a comprehensive picture of children’s early social experiences and improve studies exploring individual differences.